Intervention, stimulus control, and generalization effects of response interruption and redirection on motor stereotypy. (16th November 2018) - Gould, Kaitlin M.; Harper, Jill M.; Gillich, Emily; Luiselli, James K.
Abstract : This study evaluated the effects of response interruption and redirection (RIRD) on motor stereotypy (hand and body movements) in a child with neurodevelopmental disorders. We also assessed whether a stimulus paired with RIRD could acquire inhibitory control when tested during nonintervention conditions. Compared with baseline phases in a reversal design, RIRD decreased both hand and motor stereotypies, and there was evidence of stimulus control. Extending RIRD to a second setting was also effective. The care providers responsible for intervention implemented RIRD with fidelity, and they rated the procedure positively. Clinical and research implications from these findings are discussed.